Answer:
The domain is the set of all real numbers.Step-by-step explanation:
We know:
The root with an odd degree is exist for any real number.
The root with an even degree is exist for any non-negative real number.
The domain:
[tex]\sqrt[n]{a}[/tex]
is all real number if n is odd number.
is alle non-negative real number if n is even number.
A line passes through the points (–3, 7) and (6, 4). Which shows the graph of this line?
Step-by-step explanation:
Any line passing through (-3,7) and (6,4) is,
y-y1=(y2-y1) (x-x1)
(x2-x1)
y-7 = (4-7) (x+3)
(6+3)
y-7 = (-3/9)(x+3)
y-7= (-1/3)(x+3)
3y-21=-x-3
x+3y-21+3=0
x+3y-18=0
Which h is the required line.
Answer:
A
Step-by-step explanation:
how to solve this ? 4x+2y=6
Answer:
[1, 1]
Step-by-step explanation:
When you plug in these coordinates, you will see that 4 + 2 = 6.
I am joyous to assist you anytime.
Please help me i need help this is some of my summer school thank you
Answer:
This statement is given.Add 2 to both sides of this equation.Add [tex]-4x[/tex] to both sides of this equation.Divide both sides by 2.Apply the symmetric property of equality.Step-by-step explanation:
The unknown [tex]x[/tex] and the numbers are mixed in the given equation. However, in the desired equation, the left-hand side contains only the unknown while the right-hand side contains only numbers.
Start with the given equation. That's statement 1.
The question chooses to move the number [tex]-2[/tex] from the right-hand side of the equation to the left-hand side in statement 2. This change can be done by adding [tex]2[/tex] (the opposite of [tex]-2[/tex]) to both sides of the equation.
In statement 3, The question moves the term with the unknown [tex]4x[/tex] from the left-hand side of the equation to the right-hand side. This change can be done by adding [tex]-4x[/tex] (the opposite of [tex]4x[/tex]) to both sides of the equation.
The coefficient of the unknown [tex]x[/tex] in statement 3 is [tex]2[/tex]. In statement 4, the question turns this coefficient into [tex]1[/tex]. This change can be done by dividing both sides by the coefficient of [tex]x[/tex]. Keep in mind that multiplying both sides with the reciprocal of that coefficient, [tex]1/2[/tex], will achieve the same effect.
By the symmetric property of equality, [tex]a = b[/tex] if and only if [tex]b = a[/tex]. In other words, if [tex]3/2 = x[/tex] is true, [tex]x = 3/2[/tex] must also be true. That leads to statement 5.
Find the value of x that will make A||B
Thanks for helping. :)
Answer:
x = 20
Step-by-step explanation:
The converse of the same side exterior angles theorem states that when two same side exterior angles are supplementary, the two lines they are on are parallel.
So that means that 5x + 9 and 3x + 11 are supplementary.
Therefore, 5x + 9 + 3x + 11 = 180.
Add like terms: 8x + 20 = 180
Subtract: 8x = 160
Divide: x = 20
Answer:
*To be honest, we have a bunch of ways to find x, but I'm only going to use one.
So in order for A║B, we need the outer angle of these two lines but on the opposite sides to be equal, which means:
5x + 9 = 180 - (3x + 11)
⇔ 5x + 3x = 180 - 9 - 11
⇔ 8x = 160
⇔ x = 160/8 = 20
So x is equal to 20.
What is the measure of XYZ?
O A. 75°
O B. 56.5°
O C. 38°
O D. 76
Without additional context or a diagram, it is not possible to determine the measure of angle XYZ from the information provided.
Explanation:You have asked for the measure of angle XYZ but did not provide a specific diagram or context for angle XYZ. To determine the measure of an angle, one would typically need additional information such as the measures of other angles, the type of geometric figure involved, or an algebraic expression representing the angle.
Based on the information given, which does not directly provide an angle measure for XYZ, it is not possible to accurately determine the measure of angle XYZ. The listed measures (30.1°, 48.7°, 31.1°, 23.6°, 53.1°, etc.) represent other angles or calculations from different problems and cannot be used to infer the measure of angle XYZ without additional context.
If ((x) = 3x + 10 vand g(x) = 4x - 2, find (f - g)(x).
[tex](f-g)(x)=3x+10-(4x-2)=3x+10-4x+2=-x+12[/tex]
If f(x) =1/9 x-2, what is f-1(x)?
Answer:
f^-1(x) = 9(x+2)
Step-by-step explanation:
To find the inverse function, exchange x and y and then solve for y
y = 1/9 x -2
Exchange x and y
x = 1/9 y-2
Solve for y
Add 2 to each side
x+2 = 1/9 y-2+2
x+2 = 1/9y
Multiply each side by 9
9(x+2) = 9*1/9y
9(x+2) = y
The inverse function
f^-1(x) = 9(x+2)
Answer:
9x+18
Step-by-step explanation:
[tex]f^{-1}[/tex] means they want you to find the inverse function of y=1/9 x-2.
The inverse is just a swapping of x and y.
People tend to remake the y part the subject again because they want to write it as a function.
Let's start:
[tex]y=\frac{1}{9}x-2[/tex]
Swap x and y:
[tex]x=\frac{1}{9}y-2[/tex]
Now it's time to solve for y:
Add 2 on both sides:
[tex]x+2=\frac{1}{9}y[/tex]
Multiply both sides by 9:
[tex]9(x+2)=y[/tex]
Distribute:
[tex]9x+18=y[/tex]
So The inverse function is:
[tex]f^{-1}(x)=9x+18[/tex]
In geometry, you can use deductive rules to.
O
A. make conjectures
O
B. prove conjectures
O
C. define terms
O
D. find patterns
In geometry, you can use deductive rules to prove conjectures
What is Coordinate Geometry?A coordinate geometry is a branch of geometry where the position of the points on the plane is defined with the help of an ordered pair of numbers also known as coordinates.
Deductive reasoning is used in geometry to start with a set of given premises or axioms, and then use logical reasoning and previously established theorems to draw conclusions or prove conjectures.
The main use of deductive rules in geometry is to prove conjectures.
A conjecture is considered proven only when it has been shown that it is logically impossible for it to be false.
Hence, in geometry, you can use deductive rules to Prove conjectures
To learn more on Coordinate Geometry click:
brainly.com/question/27326241
#SPJ7
Which of the following is a geometric sequence? Help pleaseee!
=====================================
How I got that answer:
A sequence is geometric if you are able to divide any term over its prior one and get the same result each time. Note with something like choice A we have...
term2/term1 = 13/6 = 2.17 (approx) and term3/term2 = 19/13 = 1.46
the results 2.17 and 1.46 are not the same, so we can rule out choice A
---------
Choice B however, we have...
term2/term1 = 3/(-3) = -1
term3/term2 = -3/3 = -1
term4/term3 = 3/(-3) = -1
each time we get -1, so this is the common ratio. We can multiply each term by the common ratio -1 to get the next term, for instance,
term2 = (common ratio)*(term1) = -1*(-3) = 3
term3 = (common ratio)*(term2) = -1*3 = -3
and so on. This proves that sequence B is geometric. Sequences C and D are not geometric for similar reasoning to choice A.
There are 2200 students in a school. 52.5% of them are male. How many are female?
Answer:
1045 females
Step-by-step explanation:
First, lets calculate how many males there are.
52.5% of 2200 = 1155
Then, calculate the difference between the males and the total.
2200-1155=1045
Have a wonderful day!
There are 1045 female students in the school
How to determine the number of female students?The proportion of male students is given as:
Male proportion = 52.5%
This means that the female proportion is:
Female = 100% - 52.5%
Female = 47.5%
The number of female students is then calculated as:
Female = 47.5% * 2200
Evaluate
Female = 1045
Hence, there are 1045 female students in the school
Read more about proportions at:
https://brainly.com/question/1781657
#SPJ6
The boat speed in still water is 30 miles per hour. A boat travels for 3 hours downstream and returns the same distance in 5 hours.find the speed of the stream
Answer:
7.5 mph.
Step-by-step explanation:
Speed downstream = d / 3 = 30 + x where d = the distance , x =speed of the stream.
Speed upstream = d / 5 = 30 - x.
30 + x = d/3
30 - x = d/5
Adding the 2 equations
60 = d/3 + d/5
8/15 d = 60
d = 60 * 15 / 8 = 112.5 miles.
Now calculate x , the speed of the stream:
112.5 / 3 = 30 + x
x = 112.5 / 3 - 30
= 7.5 mph.
A bag contains 4 blue balls, 7 yellow balls and 4 white balls. Event A is defined as drawing a blue ball on the first draw and event B is defined as
drawing a white ball on the second draw. If two balls are drawn from the bag, one after the other and not replaced,
what is P(B|A) expressed in simplest form?
Final answer:
The conditional probability of drawing a white ball on the second draw after a blue ball has been drawn on the first draw from a bag of balls without replacement is 2/7.
Explanation:
The question asks for the probability of drawing a white ball on the second draw, given that a blue ball has been drawn on the first draw (P(B|A)) from a bag containing 4 blue balls, 7 yellow balls, and 4 white balls, without replacement.
Firstly, we calculate the total number of balls in the bag: 4 blue + 7 yellow + 4 white = 15 balls.
For event A (drawing a blue ball first), there are 4 ways this can happen out of 15 total possibilities, so the probability of A is 4/15. After a blue ball is drawn, there are now 14 balls left in the bag for the second draw.
Since event B is drawing a white ball as the second ball, given that a blue ball has already been drawn on the first draw, there are still 4 white balls left in the bag after event A has occurred. Therefore, the probability of B given A is 4/14, which simplifies to 2/7.
Thus, P(B|A) = 2/7.
Write the equation of the piecewise function ƒ that is represented by its graph.
A piecewise function is a function that is defined by several different formulas depending on the input (x). In this case, the function f(x) is a horizontal line for 0 ≤ x ≤ 20. The equation for this function would be y = constant, for 0 ≤ x ≤ 20, where the constant value is defined by the height of the horizontal line on the graph.
Explanation:To write the equation of the piecewise function that is represented by a graph, you need to identify the different segments of the function and write a mathematical expression that describes each segment. In your case, the function f(x) is a horizontal line and is only defined between x = 0 and x = 20 (both inclusive). So, if we let y = f(x) be the horizontal line, then for the domain 0 ≤ x ≤ 20, the piecewise function can be written as:
y = constant, for 0 ≤ x ≤ 20.
Note that the 'constant' value of y is defined by the height of the horizontal line on the graph. This specification assumes that there are no other pieces to the function outside the range of x = 0 to x = 20.
Learn more about Piecewise Function here:https://brainly.com/question/28225662
#SPJ12
What number must be added to the expression below to complete the square x^2+3x
Answer:
9/4
Step-by-step explanation:
x^2+3x
Take the coefficient of the x term, 3
Then divide by 2, 3/2
Then square it (3/2) ^ = 9/4
This is what you need to add to complete the square
Graph -6x-9y=54
A
B
C
D
Answer:
A.
Step-by-step explanation:
The slope would be -2/3 and the y-intercept is -6
For this case we must indicate the graph of the following equation:
[tex]-6x-9y = 54[/tex]
Adding 6x to both sides we have:
[tex]-9y = 54 + 6x[/tex]
Dividing between -9 on both sides:
[tex]y = \frac {54} {-9} + \frac{6x} {-9}\\y = -6 - \frac {2} {3} x[/tex]
For an equation of the form[tex]y = mx + b[/tex], the slope is given by "m" and the point of intersection with the y axis is "b".
In this case we have that[tex]b = -6[/tex] and[tex]m = -\frac {2} {3}[/tex]. The slope is negative. So, the corresponding graph is option A
Answer:
Option A
Write 0.00021 correct to 1 significant figure
Answer:
0.0002
Step-by-step explanation:
0.00021 is a 2 significant figure .after the decimal point the zero can be counted as a significant figure or not ,it depends
Answer:
0.0002.
Step-by-step explanation:
The first significant figure is 2 and since 1 is the second significant figure ( 1 is < 5) the 2 is retained.
which is the approximate solution for the system of equations 8x - 10y = -23 and 9x + 10y =-16
Answer:
The approximate solution is: x = -2.29; y = 0.46
Step-by-step explanation:
8x - 10y = -23
9x + 10y =-16
Since you have -10y in one equation and 10y in the other equation, add the equations to eliminate y and solve for x.
17x = -39
x = -39/17
Now substitute -39/17 for x in the first equation, and solve for y.
8(-39/17) - 10y = -23
-312/17 - 10y = -391/17
-10y = -79/17
y = 79/170
The exact solution is x = -39/17; y = 79/170
The approximate solution is: x = -2.29; y = 0.46
Using side lengths only could the triangles be similar?
Answer:
no
Step-by-step explanation:
There is no consistent scale factor.
Answer:
No
Step-by-step explanation:
For triangles to be similar there must be a proportion between their measurements.
That is, for example if from one triangle to another one side doubled, all other sides must also double.
The triangle side on the left sides measure 1.5, 1 and 2.
In the right triangle the sides measure 0.5, 1 and 1.5
There is no proportion factor that serves to convert all the measures of the first triangle to those of the second triangle.
So the triangles are not similar.
1. Which kind of triangle is shown?
A.right
B.equilateral
C.isosceles
D.scalene
ANSWER ASAP
Answer:
I believe it's a scalene triangle
D. Scalene
Hope this helps
Step-by-step explanation:
Scale = No equal sides and No equal angles
PLEASE HELP ITS TIMED
which is the graph of a logarithmic function?
Answer:
Choice D
Step-by-step explanation:
You are given for graphs.
A. This graph is translated graph of the graph of inverse proportion function
[tex]y=\dfrac{k}{x}.[/tex]
B. This graph is the graph of linear function
[tex]y=kx+b.[/tex]
C. This graph is the graph of quadratic function
[tex]y=(x-a)^2.[/tex]
D. This graph is the graph of logarithmic function
[tex]y=\log_ax.[/tex]
I really don’t understand what the questions asking? How do I solve this
Answer:
$17.85
Step-by-step explanation:
Let the dollar amount per shirt be represented by s.
Let the dollar amount per pants be represented by p.
You have the following system:
3s+2p=104.81
2s+1p=61.33
If I multiply the bottom equation by -2, I can set the system up for elimination since the equations are already and the same form and I will have 2p and -2p in the same column there. 2p+(-2p)=0
Multiplying equation 2 by -2:
3s+2p=104.81
-4s-2p=-122.66
-----------------------Add the equations:
-1s =-17.85
Multiply both sides by -1:
s=17.85
So one shirt cost $17.85
Solve the equation 225x^2+4=0
Answer:
-2i/15 and 2i/15
Step-by-step explanation:
Difference of Squares:
(15x+2i)(15x-2i)
Answers: -2i/15 and 2i/15
Genesis is using her savings account to pay standard bills over 6 months without replenishing the funds.use the table to write a linear function that models her spending
month. savings account balance in $
0 1,500
2 1,200
4 900
6 600
A. f(x)=150x+600
B. f(x) =-150+1500
C. f(x)= 1/150x+600
D. f(x) = -1/150x+1500
Answer:
B. f(x) =-150+1500
Step-by-step explanation:
Let x represents the number of months and y represents the savings account balance ( in dollars )
Thus, table would be,
x 0 2 4 6
y 1,500 1,200 900 600,
Let the linear function that represents the above table is,
y = mx + c
By the table,
1500 = m(0) + c ⇒ c = 1500,
Again by the table,
1200 = m(2) + c
1200 = 2m + 1500
-300 = 2m ⇒ m = -150
The function would be,
y = -150x +1500
Since, 900 = -150(4) + 1500
600 = -150(6) + 1500
The whole table satisfy the equation y = -150x +1500,
Hence, the linear function that models the given table is,
y = -150x +1500
Option 'B' is correct.
Answer:
b
Step-by-step explanation:
what is the solution to the equation square root 5x-7= square root 3x+5
Answer:
Step-by-step explanation:
Just as a hint. On this editor, you have to use brackets a lot. We cannot be certain what you mean. I'm going to interpret the question one way, but there are others.
√(5x - 7) = √(3x + 5)
Square both sides.
(√(5x - 7) )^2 = (√(3x + 5) )^2
5x - 7 = 3x + 5
Add 7 to both sides.
5x - 7 + 7 = 3x + 5 + 7
Combine
5x = 3x + 12
Subtract 3x from both sides.
5x - 3x = 3x -3x + 12
Combine
2x = 12
Divide by 2
2x/2 = 12/2
x = 6
This confirms that x = 6 is indeed a solution. No other solutions are found, and so x = 6 is the unique solution to the problem.
The solution to the equation (square root 5x-7)= (square root 3x+5) requires squaring both sides to eliminate the square roots and then solving the resulting quadratic equation. We begin by squaring each side:
( square root 5x-7)2 = ( square root 3x+5)2
5x - 7 = 3x + 5
We move all terms to one side to obtain a standard quadratic equation form:
5x - 3x = 5 + 7
2x = 12
x = 6
However, because we squared both sides, we must check the solution in the original equation to ensure it does not produce extraneous solutions. Substituting x = 6 into the original equation, we get:
(square root 5(6)-7) = (square root 3(6)+5)
( square root 30-7) = ( square root 18+5)
square root 23 = square root 23
This confirms that x = 6 is indeed a solution. No other solutions are found, and so x = 6 is the unique solution to the problem.
A line is in point-slope form and and passes through points (-4,-3) and (12,1) and is y-1= 1/4(x-12) what is the standard form of this equation
Answer:
x - 4y = 8Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
============================================
We have the points (-4, -3) and (12, 1).
Substitute:
[tex]m=d\frac{1-(-3)}{12-(-4)}=\dfrac{4}{16}=\dfrac{1}{4}[/tex]
Put the volume of a slope and the coordinates of the point (12, 1) to the equation of a line:
[tex]y-1=\dfrac{1}{4}(x-12)[/tex]
The standard formula of an equation of a line:
[tex]Ax+By=C[/tex]
Convert:
[tex]y-1=\dfrac{1}{4}(x-12)[/tex] multiply both sides by 4
[tex]4y-4=x-12[/tex] add 4 to both sides
[tex]4y=x-8[/tex] subtract x from both sides
[tex]-x+4y=-8[/tex] change the signs
[tex]x-4y=8[/tex]
which line is perpendicular to the given equation: y=2x+17
Answer:
[tex]\large\boxed{y=-\dfrac{1}{2}x+b,\ \text{wher}\ b\in\mathbb{R}.}[/tex]
Step-by-step explanation:
[tex]\text{Let}\ k:y=m_1x+b_1,\ l:y=m_2x+b_2\\\\l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\iff m_1=m_2\\==========================\\\\\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept\\==========================\\\\\text{We have the equation of the line:}\ y=2x+17\to m_1=2.\\\\\text{Therefore}\ m_2=-\dfrac{1}{2}.\\\\\text{The equation of a line:}\ y=-\dfrac{1}{2}x+b,\ \text{wher}\ b\in\mathbb{R}.[/tex]
SEE IMAGE! Which of the following expressions is equal to the value of x?
A) 0.9(sin50)
B) (sin50)/0.9
C) 0.9(cos50)
D) (cos50)/0.9
Answer:
A) 0.9(sin50)
Step-by-step explanation:
Since this is a right triangle, we can use
sin a = opposite side/ hypotenuse
sin 50 = x /.9
Multiply each side by .9
.9 * sin 50 = x/.9 * .9
.9 (sin 50) = x
y = 7
x + y = 6
What is the solution of the system shown?
(, 14)
(6, 12)
(10 , 5)
Answer:
(10 2/3, 5)
Step-by-step explanation:
1/2 x + 1/3y = 7
1/4x + 2/3y = 6
I do not like fractions so I will multiply the first equation by 6 and the second equation by 12 to eliminate the fractions.
6(1/2 x + 1/3y) = 7*6
Distribute
3x+2y = 42
Now the second
12(1/4x + 2/3y) = 6*12
3x+8y = 72
My system of equation is
3x+2y = 42
3x+8y = 72
Subtracting the second from the first
3x+2y = 42
-3x-8y = -72
-------------------
-6y = -30
Divide by -6
-6y/-6 = -30/-6
y =5
Substituting into 3x+2y = 42
3x+2(5) = 42
3x+10 =42
Subtracting 10 from each side
3x+10-10 =42-10
3x= 32
Dividing by 3
3x/3 = 32/3
x = 32/3 or 10 2/3
Answer:
10 2/3, 5)
Step-by-step explanation:
1/2 x + 1/3y = 7
1/4x + 2/3y = 6
I do not like fractions so I will multiply the first equation by 6 and the second equation by 12 to eliminate the fractions.
6(1/2 x + 1/3y) = 7*6
Distribute
3x+2y = 42
Now the second
12(1/4x + 2/3y) = 6*12
3x+8y = 72
My system of equation is
3x+2y = 42
3x+8y = 72
Subtracting the second from the first
3x+2y = 42
-3x-8y = -72
-------------------
-6y = -30
Divide by -6
-6y/-6 = -30/-6
y =5
Substituting into 3x+2y = 42
3x+2(5) = 42
3x+10 =42
Subtracting 10 from each side
3x+10-10 =42-10
3x= 32
Dividing by 3
3x/3 = 32/3
x = 32/3 or 10 2/3
Factor completely 4h2 + g.
The expression 4h² + g has no common factors or recognizable factoring patterns, and is thus already in its simplest form; it cannot be factored further.
To factor completely the expression 4h² + g, we would look for common factors or recognizable patterns like the difference of squares, perfect square trinomials, or other factoring techniques. However, since 4h² and g have no common factor and the expression is not a difference or sum of cubes, or any other known factoring pattern, it cannot be factored further (assuming g is a constant). In other factoring scenarios, one might look for techniques like grouping, but that's not applicable here either. Therefore, the expression 4h² + g is already in its simplest, factored form as there are no common factors between the terms.
What is the value of x to the nearest tenth?
Check the picture below.